O centro de Pai Joaquim de Angola: reflexões acerca de um lugar ritual = The center of Pai Joaquim de Angola : reflections on a ritual place - Brito, Lucas Gonçalves (Ciencias sociales y religión, 2017)
Place is a relevant aspect of the cultural construction of identities. Although place may be fundamental both as a category and a happening of people’s lived experience in different societies, its implicit theoretical statute is often disregarded. This paper aims to explore some relations between place and ritual as anthropological concepts. For this purpose, the text is composed of three parts. First, it draws a brief theoretical reflection regarding some notions of space and place. Secondly, it reports how the space and place in the temple of Umbanda religion conjugate an ancient symbolism. Finally, it describes some rites in relation to the places they happen. It is argued that the experience of the ritual is “placed” and that the sacred character of place results of the sacrality of rites themselves.